Factors associated with positive self-perception of oral health in pregnant and postpartum women - Soraya Mameluque; Felipe Mameluque; Paulo Henrique da Cruz Ferreira; Ana Iza Saraiva Rodrigues; Wellington Danilo Soares; Danilo Cangussu Mendes; Samuel Trezena (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to evaluate the associated factors with positive self-perception of oral health in pregnant and postpartum women treated at a reference maternity hospital in the north of Minas Gerais, Brazil. Methods: cross-sectional study with women assisted in an extension project. The sample consisted of women evaluated in the period from 2012 to 2022 who passedthe inclusion and exclusion criteria. The outcome variable was self-perception of oral health, which was dichotomized after the participants' response options. The analyses were performed using the SPSS 20.0 software. Results: a total of 711 women participated. The positive self-perception of oral health was present in 50.2% of the sample. The associated factors were women without a partner (PR=1.07; CI95%=1.00-1.14; p=0.042), who went to the dentist during pregnancy (PR=1,12; CI95%=1.05-1.19; p<0.001), who brushed their teeth three times or more a day (PR=1.08; CI95%=1.01-1.15; p=0.028), with no dental caries (PR=1.10; CI95%=1.03-1.18; p=0.005) and who did not notice oral changes during the gestational period (RP=1.16; CI95%=1.09-1.24; p<0.001). Conclusions: positive self-perception of oral health was associated with better oral hygiene habits and visits to the dentist during the gestational period.